Pharmacological Effects of Topical Dapsone Gel in Experimentally-Induced Thermal Injury in Rabbits - Mustafa A. Mohammed; Fouad Kadhim Gatea; Ahmed R. Abu-Raghif; Muhammed Abdul-Gabar Hamoodi Aldabagh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Burn injuries have been a global health issue due to their multiple widely present causes and the burdenof their consequences. There have been many chemical agents used topically to accelerate the burn woundhealing process and avoid developing infections but the desirable satisfactory level has not been reached.Dapsone, a century-old antibiotic with anti-inflammatory effects has been investigated as a potential topicaltreatment for burn wounds compared with standard silver sulfadiazine.Forty-two apparently male rabbits were divided into four groups each of twelve animals except for thenegative control group which was 6 animals: intact healthy animals (HA), burn without treatment as apositive control (BWT), dapsone 5% topical and silver sulfadiazine cream 1%, the latter three group’ animalswere treated twice daily for 24 days.Burn wound contraction, the levels of tumor necrosis factor-alpha TNF-a in skin tissue homogenates andhistopathological changes were assessed at days 8,16, and 24 in addition to in-vitro antimicrobial sensitivitytest.Dapsone has shown a comparable antibacterial activity against gram-positive bacteria to SSD while showingpoorer activity against gram negative bacteria.Dapsone has also shown an earlier and more significant burn size contraction compared to SSD since day8and until the end of the study and significantly lower levels of TNF-a compared to SSD while showing lowerinflammatory and higher granulation, re-epithelization and fibrosis compared to SSD in histopathologicalexamination.Our study demonstrates that dapsone is a promising candidate as a topical burn treatment due to itsantibacterial, anti-inflammatory, and wound healing properties.